The Art and Science of Teaching Agriculture Four Keys to Dynamic Learning - Whittington, M. Susie; Rudd, Rick; Elliot, Jack (Open textbook library., 2023)
The Art and Science of Teaching Agriculture: Four Keys to Dynamic Learning is a methods of teaching book. Specifically, it is a collection of thoughts, best practices, strategies, and techniques for planning, delivering, and assessing teaching and learning. This resource is assembled from among the best teaching professors in agricultural communication, education, and leadership in America. They have narrated their favorite class sessions … sessions chosen with the goal of making us all better teachers. You will quickly grasp the four fundamental keys of solid, basic, time-tested formal and nonformal teaching: Laying the Foundation, Connecting with Students, Designing Instruction, and Applying Learning. These keys are shared with you through the unique voices of the authors to provide a multiperspective approach to teaching. The authors offer both secondary and postsecondary educators in both formal and nonformal educational environments the opportunity to build confidence in planning, delivering, and assessing the depths of the variables inherent in learning. You will acquire the foundation to teach so your learners can learn dynamically. Are you reviewing or adopting this book for a course? Please help us understand your use by filling out this form: https://bit.ly/teachagriculture_interest